Spokane Chamber of Commerce and AYPE officials, Alaska-Yukon-Pacific Exposition, Seattle, Washington, May 25, 1908 - Nowell, Frank H., 1864-1950 (1908)
On verso of image: Spokane Chamber of Commerce 5/25/08 Caption on image: x80 PH Coll 727.35 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number